Multimorbidity's research challenges and priorities from a clinical perspective: The case of 'Mr Curran'. (June 2014) - Muth, Christiane; Beyer, Martin; Fortin, Martin; Rochon, Justine; Oswald, Frank; Valderas, Jose M.; Harder, Sebastian; Glynn, Liam G.; Perera, Rafael; Freitag, Michael; Kaspar, Roman; Gensichen, Jochen; et al.
ABSTRACT Older patients, suffering from numerous diseases and taking multiple medications are the rule rather than the exception in primary care. A manifold of medical conditions are often associated with poor outcomes, and their multiple medications raise additional risks of polypharmacy. Such patients account for most healthcare expenditures. Effective approaches are needed to manage such complex patients in primary care. This paper describes the results of a scoping exercise, including a two-day workshop with 17 professionals from six countries, experienced in general practice and primary care research as well as epidemiology, clinical pharmacology, gerontology and methodology. This was followed by a consensus process investigating the challenges and core questions for multimorbidity research in primary care from a clinical perspective and presents examples of the best research practice. Current approaches in measuring and clustering multimorbidity inform policy-makers and researchers, but research is needed to provide support in clinical decision making. Multimorbidity presents a complexity of conditions leading to individual patient's needs and demanding complex processes in clinical decision making. The identification of patterns presupposes the development of strategies on how to manage multimorbidity and polypharmacy. Interventions have to be complex and multifaceted, and their evaluation poses numerous methodological challenges in study design, outcome measurement and analysis. Overall, it can be seen that complexity is a main underlying theme. Moreover, flexible study designs, outcome parameters and evaluation strategies are needed to account for this complexity.